IbM KELOMPOK BIMBINGAN BELAJAR DI KELURAHAN BANDUNGREJOSARI DAN BAKALANKRAJAN KECAMATAN SUKUN MALANG JAWA TIMUR - marsuki, Marsuki; Rokhyanto, Rokhyanto; Listiani, Welas (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2017)
The study aims at forming larning group and improving students’ learning achievement of the elementary, junior, and senior schools at villages Bandungrejosari and Bakalankrajan Kecamatan Sukun Malang. The study uses quantitative-qualitative descritptive approach. The subjects are 15 local peopleas IbM cooperative partners trained to be learning counseling instructors and (2) 138 elementary , 18 junior, and 14 senior high school students joining with learning group and learning counseling at villages Bandungrejosari and Bakalankrajan kecamatan Sukun Malang. The instruments are observation sheet and test consisting of pretest and posttest. Based on the result achieved, the IbM program got extraordinary encouragement and symphaty from local people, villages, schools, and social leaders. The learning counseling activity was going on for 3 months from September 1 to November 29, 2014. Based on the test analysis, it was found that learning group formation by providing learning counseling could give significant influence which could be shown in that the mean of the posttest was higher than that of pretest for the students of elementary, junior, and senior schools at villages Bandungrejosari and Bakalankrajan kecamatan Sukun Malang.